P100 Designing and implementing a COPD discharge care bundle. (2nd December 2011) - Hopkinson, N S; Englebretsen, C; Cooley, N; Kennie, K; Lim, M; Woodcock, T; Laverty, A; Wilson, S; Elkin, S L; Caneja, C; Falzon, C; Burgess, H; et al.
Abstract : Problem: Acute exacerbations of COPD are a major cause of hospital admission and readmission. National surveys have revealed significant differences in patient outcomes which are likely to be due to variations in care. Design: A care bundle, comprising a short list of evidence-based practices to be implemented prior to discharge for all patients admitted with this condition was developed, based on a review of National Guidelines and other relevant literature, expert opinion and patient consultation. Implementation was then piloted using action research methodologies in an urban acute hospital. Key measures for improvement: Improvements in process measures based around the items in the care bundle were the provision of smoking cessation advice, referral for pulmonary rehabilitation, and review of inhaler technique. A 72 h post-discharge phone call was evaluated. Data from the first year of the bundle were compared with the year prior to its initiation including 30-day readmission rate. Strategies for change: The care bundle was launched with events to ensure staff awareness. Weekly meetings were held with review of bundle compliance so that areas for attention could be addressed promptly. A plan, do, study, act (PDSA) cycle approach was used. Examples included ongoing support to develop ward nurses' knowledge of correct inhaler use, nurses attending pulmonary rehabilitation sessions and the use of a "safe discharge" checklist. Effects of change: Referral to pulmonary rehabilitation increased by 158% and compliance with assessment for smoking cessation was 100%. Nurse confidence in inhaler technique improved. Roughly 10% of post discharge phone calls identified a cause for concern. The 30-day readmission rate was 10.8% for patients where the bundle was used (n=94) compared to 16.4% where it was not (n=365) (95% CI for difference −2.1% to 13.2%). The bundle has been accepted onto the list of CQUIN measures by London SHA and is being rolled out to further sites. Lessons learnt: Actively involving all staff is vital to ensure that the changes introduced are understood and the process followed. Implementation of a care bundle has the potential to produce a dramatic improvement in compliance with optimum health care measures.